Benchmarking the practices of the centers of technical excellence : basis of a development framework for technical-vocational schools in Ilocos Norte - Bagaoisan, Michel B. (Laoag City : [s.n.], 2018)
The study formulated and validated a development framework for Technical- Vocational schoold based on the results of the benchmarking process involving the Centers of Technical Excellence. The research and development (R and D) methodology with three major stages, namely: planning, developmemt and validation was used . Benchmarking was conducted at the Centers of Technical Excellence in Ilocos Norte, Region l in the four major areas of Technical-Vocational Education: Agricultural Crops Production, Aquaculture, Automotive Servicing and Electronics Servicing. The Benchmark schools were selected from the technical-vocational schools in the divisions of Ilocos Norte and Laoag City.
Bibliography: pages 303-307.
CHED-La Union
Keywords: Technical education